2023
DOI: 10.1108/ijqrm-08-2021-0290
|View full text |Cite
|
Sign up to set email alerts
|

The structural link between TQM practices and financial performance: the mediating role of operational performance

Abstract: PurposeThis study aims at examining the effect of total quality management (TQM) practices on the financial performance ISO 9001:2008 certified manufacturing companies in Ethiopia with a mediating role of operational performance.Design/methodology/approachA cross-sectional survey research was conducted to meet the purpose. Data used for the study were solely primary data and were collected from the top and middle-level managers of different departments and senior experts working under the production/operation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 142 publications
2
3
0
Order By: Relevance
“…This result is consistent with the results obtained by (Pambreni et al., 2019; Androwis et al. , 2018) which argued that the principal role of TQM enhances quality performance, also, this result is consistent with the results obtained by (Adem and Virdi, 2023; Rawashedeh, 2018; Wei et al. , 2017) which showed that TQM practices improve operational performance.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This result is consistent with the results obtained by (Pambreni et al., 2019; Androwis et al. , 2018) which argued that the principal role of TQM enhances quality performance, also, this result is consistent with the results obtained by (Adem and Virdi, 2023; Rawashedeh, 2018; Wei et al. , 2017) which showed that TQM practices improve operational performance.…”
Section: Discussionsupporting
confidence: 92%
“…The more industries adopt TQM practices, the more likely they are to enhance their performance. This result is consistent with the results obtained by (Pambreni et al, 2019;Androwis et al, 2018) which argued that the principal role of TQM enhances quality performance, also, this result is consistent with the results obtained by (Adem and Virdi, 2023;Rawashedeh, 2018;Wei et al, 2017) which showed that TQM practices improve operational performance. On another side, our findings give another report regarding the impact of TQM on OP in the Tunisian context.…”
Section: The Effect Of Contextual Variablesupporting
confidence: 92%
See 3 more Smart Citations